2018
DOI: 10.1111/coa.13255
|View full text |Cite
|
Sign up to set email alerts
|

The influences of age, gender and geometric pattern of visual image on the verticality perception: A subjective visual vertical (SVV) study among Malaysian adults

Abstract: Objectives: Subjective visual vertical (SVV) is a simple, quick and reliable test for measuring utricular function. The literature on the effects of fundamental demographic variables such as age and gender on SVV is inconclusive and should be supported by research with larger samples. The aim of the present study was to determine the influences of age, gender and geometric pattern of visual image on SVV among healthy adults. Study Design: This study employed a repeated measures design. Settings: Otorhinolaryng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Despite well-documented findings regarding the aging effect on the vestibular system [ 17 – 23 ], we found no effect of age on SVV. Such results support previous studies that showed that spatial accuracy for SVV is not impaired nor intensified with age [ 26 28 ]. However, our results are in disagreement with the results reported by Baccini et al [ 25 ], who reported that static SVV measurements were age-dependent and that older participants had more difficulty in judging the absolute vertical, resulting in larger deviations from the true vertical.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite well-documented findings regarding the aging effect on the vestibular system [ 17 – 23 ], we found no effect of age on SVV. Such results support previous studies that showed that spatial accuracy for SVV is not impaired nor intensified with age [ 26 28 ]. However, our results are in disagreement with the results reported by Baccini et al [ 25 ], who reported that static SVV measurements were age-dependent and that older participants had more difficulty in judging the absolute vertical, resulting in larger deviations from the true vertical.…”
Section: Discussionsupporting
confidence: 92%
“…e functional consequence of decline in the function of the otolith organs includes age-dependent reduction in afferent signals to the integrating centers for SVV within the central nervous system, and consequently reduced sensitivity to gravity and linear acceleration [22,23]. Despite this age-dependent deterioration, reports on age-dependent modulation of SVV are inconsistent [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…reported that a 30 head roll-tilt tends to tilt the SVV in the opposite respectively. The HU-SVV was not influenced by age, as reported previously, 33,34 and HTPG laterality demonstrated similar characteristics. In contrast, the HTPG, indicating the magnitude of gravity perception, was significantly larger in middle-aged and elderly than in young participants.…”
Section: Discussionsupporting
confidence: 88%
“…Age and gender are important fundamental variables in clinical studies. As such, depending on the study outcomes, specific normative data based on age or gender might be required to enhance the diagnostic accuracy of a specific clinical tool (Jalaei et al, 2017;Zakaria et al, 2018). In the present study, a (Clemis and Sarno, 1980;Hall, 2007).…”
Section: Discussionmentioning
confidence: 97%